Analisis Penerapan K3 dalam Pelaksanaan Bongkar Cargo Special Handling di PT. Terminal Petikmas Surabaya - Putri, Ristin Alfariza; Rahayu, Trisnowati; Sri Wahyuni, Anak Agung Istri; Dahri, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
It is important to review the use of auxiliary equipment in unloading special handling containers and the implementation of K3, so that unwanted incidents do not occur in loading and unloading activities at the Surabaya Container Terminal. The purpose of this study is to find out the application of K3 in Cargo special handing unloading activities in accordance with regulations, to find out the potential risk of accidents that occur during Cargo special handling unloading activities at PT. Surabaya Container Terminal. The method used is qualitative descriptive in the form of words or pictures so that it is easy to understand by others. The data sources and data collection techniques in this study are primary data from interviews, observations and secondary data sources obtained from journals, interns, and previous research. The data analysis techniques used used used data collection, data reduction, data presentation, and conclusion drawn. The results of this study are the application of K3 and the potential risk of work accidents during Cargo Special Handling Unloading activities at PT Terminal Petikemas Surabaya. The application of K3 in Cargo Special handling unloading activities is in accordance with existing regulations because it has used the auxiliary equipment that has been provided, but there are still some accidents that occur caused by human and environmental factors.